Isolation and Identification of Cytotoxic Compounds Present in Biomaterial Life® - Ferreira, Maria Beatriz (2022)
Direct pulp capping consists of a procedure in which a material is directly placed over the exposed pulp to maintain dental vitality. Although still widely used in clinical practice, previous in vitro studies found that the biomaterial Life® presented high cytotoxicity, leading to cell death. This study aimed to identify the Life® constituents responsible for its cytotoxic effects on odontoblast-like cells (MDPC-23). Aqueous medium conditioned with Life® was subjected to liquid-liquid extraction with ethyl acetate. After solvent removal, cells were treated with residues isolated from the organic and aqueous fractions. MTT and Trypan blue assays were carried out to evaluate the metabolic activity and cell death. The organic phase residue promoted a significant decrease in metabolic activity and increased cell death. On the contrary, no cytotoxic effects were observed with the mixture from the aqueous fraction. Spectroscopic and spectrometric methods allowed the identification of the toxic compounds. A mixture of the regioisomers ortho, para, and meta of N-ethyl-toluenesulfonamide was identified as the agent responsible for the toxicity of biomaterial Life® in MDPC-23 cells. These findings contribute to improving biomaterial research and development.